ACCEPTANCE OF CRYPTOCURRENCY IN THAILAND - Kasemrat, Rattapol; Kraiwanit, Tanpat (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2023)
Even though cryptocurrency is not yet legalised in Thailand nor a legal tender, the popularity of trading in cryptocurrency has risen from time to time in the market. From the perspective of financial firms or institutions, there are opportunities to establish financial services/products based on cryptocurrency investment in anticipation of the legalisation of cryptocurrency trading by the Bank of Thailand (BOT) and the Securities and Exchange Commission, Thailand (SEC Thailand). In the past few years, Asian countries, such as China, Japan, Vietnam and Singapore, have widely invested in cryptocurrencies in order to obtain a return on investment. Many countries, including Thailand, are aware of cryptocurrencies, especially in terms of taxation, Initial Coin Offering (ICO), legalisation and control and scamming. This study focuses on providing a deep analysis of the perceptions of Thai cryptocurrency investors. The investors’ demographic characteristics of gender, age, occupation, education level and income were examined as control variables. The data analysis was based on 898 respondents in Thailand and used a binary regression model. Based on the research, age, gender and income have a significant influence on cryptocurrency adoption. An increase of one unit of income will increase the adoption rate by 1.256.